2021
DOI: 10.1027/1864-9335/a000461
|View full text |Cite
|
Sign up to set email alerts
|

Laypeople’s Belief of the Influence of Thank-You Gifts on Charitable Giving

Abstract: Abstract. Although offering gifts to encourage prosocial behaviors is a popular daily strategy, its underlying mechanism remains unknown. This study investigated the effect of thank-you gifts on charitable giving in laypeople’s beliefs ( N = 1,293). Study 1 showed that laypeople believe thank-you gifts increase charitable giving. Study 2 found that laypeople believe thank-you gifts increase both charitable giving and positive emotions of donors. Study 3 further showed that laypeople’s anticipation of donors’ e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Ten years later, as today, the paper is still a milestone that researchers would refer to when they study altruism and gift in a donation. For example, Huang et al (2021) followed their study to further investigate laypeople's belief of the influence of thank-you gifts on charitable giving, which confirmed that laypeople believe thankyou gifts would raise charitable donations and one mediation of the effect is anticipated positive emotion; another study found that thank you gifts increase (decrease) the weight that donors place on self-interested (prosocial) motives, leading to changes in donation patterns as the gift may activate mindsets or norms that emphasize self-interested motives instead of more prosocial, other-regarding motives (Chao and Fisher, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Ten years later, as today, the paper is still a milestone that researchers would refer to when they study altruism and gift in a donation. For example, Huang et al (2021) followed their study to further investigate laypeople's belief of the influence of thank-you gifts on charitable giving, which confirmed that laypeople believe thankyou gifts would raise charitable donations and one mediation of the effect is anticipated positive emotion; another study found that thank you gifts increase (decrease) the weight that donors place on self-interested (prosocial) motives, leading to changes in donation patterns as the gift may activate mindsets or norms that emphasize self-interested motives instead of more prosocial, other-regarding motives (Chao and Fisher, 2022).…”
Section: Introductionmentioning
confidence: 99%